A model for fermionic dark matter addressing both the CDF MW and the (g − 2)μ anomalies - Arcadi, Giorgio; Djouadi, Abdelhak (Frontiers in Physics, 2023)
We explore a simple and renormalizable model which incorporates a new stable fermion that accounts for the dark matter in the universe and which, at the same time, provides an interpretation of two recent measurements that deviate from the expectation in the Standard Model: the muon anomalous magnetic moment and the mass of the W-boson recently performed by the CDF collaboration. The model has a fermionic sector that involves a singlet and a doublet fields and in which the lightest state is the DM and interacts mainly through the Higgs portal. Two realizations of such a possibility are considered: one in which the Higgs sector is minimal and another in which it is extended to contain two doublet fields.